ESTIMATION OF GENETIC DISTANCE AND THE DISTINGUISHING FACTOR OF THE HORSES IN NORTH SUMATRA THROUGH MORFOMETRIC ANALYSIS - H Kaban; Hamdan Hamdan; T H Wahyuni; N Ginting; A H Daulay (Universitas Sumatera Utara, 2017)
Abstract.This research objectives to investigate the distance of genetics and differentiator factor of the horses in four District in North Sumatra. This research was conducted in Karo District (60 heads), Humbahas District (77 heads), Tapanuli Utara District (52 heads) and Samosir District (42 heads) at July 2016. The analysis used were descriptive analysis, discriminant analysis, canonical analysis, principal component analysis, genetic distances and filogenic tree. The observed variables in this study were shoulder height, hip height, hip width, body length, chest circumference, chest and chest width, and the variables that distinguish the horse in term of size were hip height and in terms of shape was the width of the chest. The nearest genetic distance was the horse between Karo and North Tapanuli District (0.869) and the horse that had the farthest genetic distance were horses in Karo District with horses in Samosir District (14.539). Based on the results of morphometric measurements of horses in this study, in order to obtain heterosis, it was expected to cross between horses in Karo District and horse in Samosir District. Keywords: morphometric, discriminant analysis, canonical analysis, principal component analysis, genetic distance